The Influence of Age and Parental Education Level on Financial Literacy Among Management Study Program Students at Nort Sumatra Islamic University - Tiara Gusti Saharani; Khairunnisak Khairunnisak; Syafrida Hanif Sahir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Low financial literacy is caused by several factors. Research related to financial literacy in the Management Study Program of the Islamic University of North Sumatra is still rarely conducted so it is necessary to discuss and analyze what factors can influence financial literacy in the study program. This study uses a descriptive research method with the research approach used by the author is quantitative research. This approach uses a quantitative approach because it uses numbers, starting from data collection, data interpretation, and presentation of results. Based on the significance value (Sig.) in the F test, it can be concluded that the hypothesis is accepted. This means that Age (X1), and Parental Education Level (X2) simultaneously (together) have a significant effect on the Financial Literacy variable (Y). Based on the magnitude of the determination coefficient (R Square) of 0.902 or equal to 90.2%. This figure means that the variables Age (X1), and Parental Education Level (X2) simultaneously (together) influence the Financial Literacy variable (Y) by 90.2%. Management study program students are expected to be able to better understand Financial Literacy because this will be knowledge in the future and is also very important for the role of parents. The Adjusted R Square level reached 89.9% and the remaining 10.1% was influenced by other variables outside this regression equation or variables that were not studied or significant